Lead-free tin-halide perovskite solar cells with 13% efficiency. (August 2020) - Nishimura, Kohei; Kamarudin, Muhammad Akmal; Hirotani, Daisuke; Hamada, Kengo; Shen, Qing; Iikubo, Satoshi; Minemoto, Takashi; Yoshino, Kenji; Hayase, Shuzi
Abstract: Despite the similarities of the optoelectronic properties between tin halide and lead halide perovskites, the performance of tin perovskite solar cells (PSCs) is still far below that of lead PSCs with highest reported efficiency to date of around 10%. This is due to the chemical instability of tin halide perovskite crystals and the energy band levels mismatch between the perovskite and charge transport layers. In this work, tin halide PSCs with efficiency of more than 13% has been fabricated by regulating the A site cation to achieve a tolerance factor of nearly 1. The partial substitution of formamidinium cation with ethylammonium cation affords a more stable tin perovskite crystal and at the same time suppresses the trap density by as much as 1 order of magnitude. Furthermore, the more favourable energy levels of the EA-substituted tin perovskites enhanced the charge extraction process into the charge transport layers and thus reducing the charge carrier recombination. This work provides a proof that tin-halide PSCs has the potential to compete with more toxic lead-based PSCs, and hopefully will pave the future direction for fabricating more efficient and stable lead-free PSCs. Graphical abstract: Simultaneous band energy alignment and trap site passivation has been achieved by regulating the A-site cation of tin halide perovskites. As a result of efficient charge extraction due to low lattice disorder, a high efficiency of 13.24% with a V OC of 0.84 V has been achieved for tin-based perovskite solar cells. Image 1 Highlights: Tin perovskite with small lattice strain and tolerance factor close to 1 achieved with ethylammonium substitution. Matching energy levels of perovskite and charge transport layers with optimal substitution of small ethylammonium. Significant improvement in electron lifetime and open-circuit voltage obtained via effective trap passivation. Record efficiency of 13.24 % for lead-free perovskite solar cell demonstrated with mixed cation and surface passivation.